Social Engagement as an Educational Outcome in a Catholic Higher Education Institution: The Role of Organizational Membership - French Reah Joy L Nunieza; Jerica May O Pillado; Nikka Marie G Salmorin; Silver Angelen V Victoriano; RJ Erika V Berdin; Paul Markku Arnel P Bautista; Daniel S Fernando (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study assessed the level of social engagement among third-year college students in a Catholic Higher Education institution during the Academic Year 2025-2026. It examined significant differences in social engagement among respondents when grouped by demographic profile. The study sought to contribute to Integrated Social Science Education by determining the extent to which these dimensions represent educational outcomes. Methodology: It utilized a quantitative design, specifically a descriptive- comparative approach. The study was conducted with a clustered, randomly sampled group of 226 third-year students.  In gathering the data, a validated, reliability-tested 20-item modified questionnaire was used. In analyzing the data, descriptive and comparative analyses, specifically mean, standard deviation, Mann-Whitney U, and Kruskal-Wallis H tests were used. Main Findings: Overall, respondents exhibited high engagement (M=2.74, SD=0.47). The results showed no significant differences in social engagement when grouped by sex [U=5989.000, p=0.441] and program [χ²(16)=25.688, p=0.059]. Meanwhile, there is a significant difference when grouped according to membership in any organization [U=4293.500, p=0.027]. These findings suggest that Integrated Social Science Education, complemented by organizational participation, plays a vital role in promoting civic learning, active citizenship, and the holistic development of socially responsible students in Catholic higher education. Novelty/Originality of this study: The novelty of this study stems from its examination of social engagement through the dimensions of political interest, social analysis, valuing applicability, and self-efficacy as educational outcomes of Integrated Social Science Education in Catholic higher education. The findings provide evidence to inform enhancements to student development programs, co-curricular activities, and community engagement initiatives that support the institution's mission of holistic formation and promote social responsibility and active citizenship among higher education students.